The impact of the African Charter on human and people's rights and the protocol on the rights of women on the South African Judiciary - Van der Poll, Letitia (University of Pretoria, 2012)
Prepared under the supervision of Dr. Letitia van der Poll, Faculty of Law of the University of the Western Cape, South Africa